6y-1y-12=

Simple and best practice solution for 6y-1y-12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-1y-12= equation:


Simplifying
6y + -1y + -12 = 0

Reorder the terms:
-12 + 6y + -1y = 0

Combine like terms: 6y + -1y = 5y
-12 + 5y = 0

Solving
-12 + 5y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 5y = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 5y = 0 + 12
5y = 0 + 12

Combine like terms: 0 + 12 = 12
5y = 12

Divide each side by '5'.
y = 2.4

Simplifying
y = 2.4

See similar equations:

| =6z-(3z-6)+(7-8z) | | 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 |

Equations solver categories